PERLINDUNGAN HUKUM PEMEGANG HAK CIPTA KARYA SINEMATOGRAFI TERKAIT ADANYA DUGAAN PELANGGARAN HAK EKONOMI MELALUI APLIKASI SOSIAL MEDIA TELEGRAM (DITINJAU DARI UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA) - Gabriel Lusia; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2021)
Uploading a creation in a social media app is evidence that the internet presence has become an impact in the modern era that keeps getting sophisticated . However, it can't be denied that it can cause several problems, with the occurrence of speculation violating economic rights especially for cinematography copyrights holders. This research used legal protection as a discussion point to cinematographic copyright holders, illegality reasons, and legal efforts that cinematographic copyright holders can use against hijackers that are using Telegram applications. The research method that is used is to regulate justice through the use of legal methods and conceptual methods. The result of the research conclude that cinematographic copyright protection in the form of preventive measures, alternative dispute solution with arbitration or repressive dispute resolution methods taken through the court. The reason why hijackers use the telegram application is because it is convenient, free and also Telegram doesn't have strict rules against misused channel. The cinematographic copyright holder that has been hijacked from the Telegram application can make an effort by giving a complaint about copying and hijacking to relevant instances.